TEACHING A FOREIGN LANGUAGE IN THE SYSTEM OF DISTANCE LEARNING - HIKMATOVA MOKHIRA AKMAL QIZI (International Journal of Innovations in Engineering Research and Technology, 2021)
This article presents the possibilities and benefits of distance learning. Also, the article is devoted to distance learning, which implies an individually differentiated approach to learning foreign language. The author believes that this form of training allows the student to choose the time and place for training, as well as to use new information technologies in training, to carry out various joint projects with students from other regions. Information technologies of distance learning allow conducting classes in a foreign language in a videoconference mode and provide controlled independent work of students.